Basic Medical Sciences Knowledge Retention for Clinical Practice - Goshu BT (Advances in Medical Education and Practice, 2022)
Bahiru Tenaw Goshu Department of Anatomy, School of Medicine, University of Gondar, Gondar, EthiopiaCorrespondence: Bahiru Tenaw Goshu, Tel +251982076296, Email haikutena@gmail.comBackground: The basis for studying the clinical sciences is the recall and comprehension of basic medical science facts. Do not, however, directly alter clinical information and as studies revealed that there are basic sciences knowledge retention of medical students gaps in clinical practice. The purpose of this study was to assess medical students’ basic medical sciences knowledge retention and a relevance of basic sciences knowledge for clinical for practice.Methods: An institutional-based descriptive cross-section epidemiological study design was carried out in the University of Gondar from April to May of 2021. A total of 15 basic and clinical sets of questions were used for data collection. The data were entered and analyzed using SPSS version 20 to analyze data.Results: A total of 191 medical students participated with response rate of 100%. Of these, 48.6% were male. Of all participant students, 69 (36.1%) have had the academic status of excellent with a commutative grade point average greater that 3.6 out of 4.0. Students who correctly responded for all categories of questions for basic and clinical sciences were 8.6± 2.7 and 5± 2.8 of second years, 5.5± 2.3 and 7.1± 1.2 of fourth years, 6.5± 1.4 and 6.7± 1.0 of fifth years, 5.3± 0.8 and 8.4± 2.5 of sixth years, respectively. As a representative year, the score of second year students’ performance for the basic sciences is a statistically significant with overall impact of the basic sciences (6.49± 2.5, F=12.51, P≤ 0.001) and clinical sciences (4.0± 1.9, F=14.73, P≤ 0.001).Conclusion: It is proposed that basic sciences knowledge should be aligned with clinical sciences preparation so that students may grasp disease diagnosis and treatment concepts in an integrated manner.Keywords: basic sciences, clinical sciences, knowledge retention, medical students